Economic evaluations of rotavirus immunization for developing countries: a review of the literature. (July 2011) - Tu, Hong-Anh T; Woerdenbag, Herman J; Kane, Sumit; Rozenbaum, Mark H; Li, Shu Chuen; Postma, Maarten J
Diarrhea is a leading cause of mortality for children under 5 years of age, and rotavirus is identified as the main cause of severe diarrhea worldwide. Since 2006, two rotavirus vaccines, Rotarix and Rotateq, have been available in the market. These vaccines have proved to have high efficacy in developed countries. Clinical trials are being undertaken in Asia and Africa, and early clinical results found that the vaccine significantly reduces severe diarrhea episodes due to rotavirus (48.3% for Asia and 30.2% for Africa). The WHO recommended that rotavirus immunization be included in all national immunization programs. Based on WHO''s recommendations, the Global Alliance for Vaccines and Immunization decided to provide financial support for rotavirus immunization in the developing world. In this article, we attempted to ascertain the cost––effectiveness of universal rotavirus immunization in developing countries. After an extensive literature search, we identified and evaluated 15 cost––effectiveness studies conducted in the developing world. The results from these studies showed that rotavirus immunization is a cost-effective strategy and one of the best interventions to prevent rotavirus-related diarrheal disease. However, rotavirus vaccines are expensive and the vaccine price appears to be the most challenging and crucial factor for decision-makers regarding whether to introduce this vaccine into developing countries'' immunization schedules. All the studies concluded that rotavirus immunization is cost effective but may not be affordable for the developing world at present. Developing countries will definitely rely on financial support from international organizations to introduce rotavirus vaccination. It is recommended that more research on cost-effective rotavirus immunization with updated data be conducted and new rotavirus vaccine candidates be developed at a cheaper price to speed up the introduction of rotavirus immunization to the developing world.